2023
DOI: 10.3390/ijms25010147
|View full text |Cite
|
Sign up to set email alerts
|

Myrsinane-Type Diterpenes: A Comprehensive Review on Structural Diversity, Chemistry and Biological Activities

Eduarda Mendes,
Cátia Ramalhete,
Noélia Duarte

Abstract: Euphorbia species are important sources of polycyclic and macrocyclic diterpenes, which have been the focus of natural-product-based drug research due to their relevant biological properties, including anticancer, multidrug resistance reversal, antiviral, and anti-inflammatory activities. Premyrsinane, cyclomyrsinane, and myrsinane diterpenes are generally and collectively designated as myrsinane-type diterpenes. These compounds are derived from the macrocyclic lathyrane structure and are characterized by havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 109 publications
(313 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the reaction occurred with high regio- and diastereoselectivity ( Scheme 3 ). Contrary to the Fe-mediated cyclization of Euphorbia factor L 3 [ 21 ], premyrsinane 5 was obtained at room temperature as only one diastereoisomer, with the same stereochemistry at C-6, C-12, and C-13 than most naturally occurring premyrsinane-type diterpenoids [ 10 ]. Our newly developed protocol would represent the first report of a biomimetic cyclization of a 6,17-epoxylathyrane into premyrsinane derivative.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the reaction occurred with high regio- and diastereoselectivity ( Scheme 3 ). Contrary to the Fe-mediated cyclization of Euphorbia factor L 3 [ 21 ], premyrsinane 5 was obtained at room temperature as only one diastereoisomer, with the same stereochemistry at C-6, C-12, and C-13 than most naturally occurring premyrsinane-type diterpenoids [ 10 ]. Our newly developed protocol would represent the first report of a biomimetic cyclization of a 6,17-epoxylathyrane into premyrsinane derivative.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this strategy has not been used for the functionalization of non-activated positions of premyrsinane-type diterpenoids. Studies of the biological activities of premyrsinanes are scarce in the literature; this is likely because of the reduced amount of the isolated compounds [10]. Nevertheless, several studies have reported that premyrsinanes possess promising anticancer [17][18][19], multidrug resistance reversal [20], and anti-inflammatory activities, inhibiting the lipopolysaccharideinduced NO production [21].…”
Section: Scheme 1 Biogenetic Relationship Between Lathyranes and Prem...mentioning
confidence: 99%
See 3 more Smart Citations